2012
DOI: 10.1177/0954407012447761
|View full text |Cite
|
Sign up to set email alerts
|

Development of a new method to assess fuel saving using gear shift indicators

Abstract: European regulations set the emissions requirements for new vehicles at 130 g CO 2 /km, with an additional 10 g CO 2 /km to be achieved by additional complementary measures, including gear shift indicators. However, there is presently little knowledge of how much fuel or CO 2 could actually be saved by the introduction of gear shift indicators, and there is no consensus on how these savings should be quantified. This study presents a procedure which allows these savings to be quantified over a New European Dri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 5 publications
0
13
0
Order By: Relevance
“…The vehicle's on-board computer is used to calculate the best gear, depending on the current speed, load and throttle position. Then, the most suitable gear is displayed by the indicator [10]. For simulation purposes it is assumed that the driver would follow the gear shift indicator or an automatic shifting system is employed.…”
Section: The Intervening Gear Ratiosmentioning
confidence: 99%
See 2 more Smart Citations
“…The vehicle's on-board computer is used to calculate the best gear, depending on the current speed, load and throttle position. Then, the most suitable gear is displayed by the indicator [10]. For simulation purposes it is assumed that the driver would follow the gear shift indicator or an automatic shifting system is employed.…”
Section: The Intervening Gear Ratiosmentioning
confidence: 99%
“…CO 2 emissions could also be reduced by 4.5% during the NEDC [9]. Norris et al [10] showed that the gear shift indicator is able to reduce the fuel consumption by 4% and 7% for a MINI Cooper and a Ford Transit van respectively. The Volkswagen Golf tested in the same paper showed little improvement [10].The fuel savings depend highly on the vehicle and the shifting strategy.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Since minimizing engine speed is critical to the goal of reducing fuel consumption [18], it was decided to include a gear shift indicator (GSI). As many modern vehicles are equipped with GSIs as standard, the vehicle's own gear shift signal was used where available on the CAN bus.…”
Section: A System Designmentioning
confidence: 99%
“…As described by [6] the use of gear shifting indicators, composed of light and/or sound alarms connected to a software that manage the gear shifting process, results in 3.6% of fuel economy in a vehicle submitted to the New European Driving Cycle -NEDC. With the same purpose, [7] developed a driving assistance system to help drivers giving fuel efficiency guidelines according with the current vehicle situation.…”
Section: Introductionmentioning
confidence: 99%